Shock & Vibration, Aircraft/Aerospace, Energy Harvesting, Acoustics & Optics, Volume 9 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Brandt, Anders; Singhal, Raj.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Shock Vibration, Aircraft /Aerospace, Energy Harvesting, Acoustics Optics, Volume 9. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the ninth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early fi ndings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: < • Energy Harvesting • Adaptive Support • Shock Calibration • Operating Data Applications • Aerospace Testing Techniques • Aircraft /Aerospace Applications • Joints • Acoustics & Optics • Other Sensing.
1 Improved Cutting Force Measurements in Milling Using Inverse Filtering -- 2 Use of a Depth Camera as a Contactless Displacement Field Sensor -- 3 Uncertainty of Digital Image Correlation with Vibrating Deformable Targets -- 4 Physical Vibration Simulation of an Acoustic Environment with Six Shakers on an Industrial Structure -- 5 Developing Conservative Mechanical Shock Specifications -- 6 Force Limited Vibration using the Apparent Mass Method -- 7 Harmonic Force Excitation Analysis of a Small-Body Asteroid/Satellite System -- 8 A Study on the Dynamic Interaction of Shock Response Fixtures and Test Payload -- 9 Modal Analyses and Experimental Verifications of Joined-wing Configurations -- 10 Modal Testing of James Webb Space Telescope (JWST) Optical Telescope Element (OTE) -- 11 Quantification of Dynamic Differences Between Boundary Conditions for Environment Specification Improvement -- 12 Modal Updating of Tail of a Military Helicopter -- 13 Modeling of High Frequency Shock Tests -- 14 A NovelMethod to Correlate a Rocket Launcher Finite Element Model Using Experimental Modal Test Measurements and Identification Algorithms -- 15 Numerical Studies on the Reduced Order Modeling of Frictionless Joint Contact Interfaces -- 16 Structural Design with Joints for Maximum Dissipation -- 17 A Hybrid Piezoelectric and Electrostatic Vibration Energy Harvester -- 18 Design of Scaled-Down Composite I-beams for Dynamic Characterization in Subcomponent Testing of a Wind Turbine Blade.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Aerospace engineering; Astronautics; Energy harvesting; Multibody Systems and Mechanical Vibrations; Aerospace Technology and Astronautics; Energy Harvesting